PENGGUNAAN MEDIA GRAFIS DAN MEDIA MODEL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK BIDANG SENI RUPA KELAS X IPA-5 DI SMA NEGERI 13 PADANG - Kerlina Marsatika; Zubaidah Zubaidah (Serupa The Journal of Art Education, 2020)
This research is based on the low learning outcomes of students who are factored by the ineffective learning media by using simple writing and sketches on the written board during the learning process. To solve this problem, you can use graphic media and media models. The type of research used is classroom action research (PTK) with students of class X IPA-5. at SMA Negeri 13 Padang as the subject. The research objective was none other than to improve learning outcomes in the class under study. The implementation is in two cycles (2x meetings). The results of the study in the first cycle with an average of 80.05, an average increase of 86.11 in cycle II. the result of the number of cycles I is 24 people complete and 12 people incomplete. In cycle II, the number of students has increased to 35 complete and 1 person incomplete. The conclusion is that using graphic media and media models is proven to improve learning outcomes of students in the field of Fine Arts.Kata Kunci : Media Grafis , Media Model, Hasil Belajar Seni Rupa